Trial without Catheter in Acute Retention of Urine secondary to Prostatomegaly - Khadka, Digbijay Bikram; Sharma, Anup; Maharjan, Prabir (Journal of Nepalgunj Medical College, 2021)
Introduction: Acute Retention of Urine is one of the main presentations for Benign Prostatic hyperplasia. Trial without catheter is an ambulatory care protocol. The greater morbidity and mortality associated with emergency surgery, and the potential morbidity associated with prolonged catheterization have led to the increasing use of a trial without catheter. Trial without catheter involves catheter removal allowing patients to void successfully so that surgery can be performed at a later stage. Use of an alpha (1)-blocker before a Trial without catheter has demonstrated that it increases its success. Aims: Identifying the success and failure of Trial without Catheter in patients with Benign Prostatic Hyperplasia and evaluating factors influencing them. Methods: A total of 60 patients who presented with acute urinary retention were enrolled in this study at Nepalgunj Medical College which was conducted between February 2021 and August 2021. All the patients underwent Foley Catheterization. Tablet Alfuzosin 10mg one tablet at night and requested follow-up after a week. Trial without Catheter conducted and the amount of urine measured after removal of the Foley catheter. Results: The study evaluated various factors predicting success of Trail without Catheter. Age group of 61-70years had higher success. Patients with moderate American Urological Association score had higher success rates than the rest. About 10 (6%) patients had a Quality of Life of less than four. The prostate volume ranging from 30-39ml had higher success rates. Patients with Grade III Intravesical Prostatic Protrusion had fewer chances of successful Trial without Catheter. Duration of Lower Urinary Tract Symptoms less than six months was favorable for the success of Trial without Catheter. Thirty five (58.3%) patients voided more than 200ml during Trial without Catheter. Conclusion: Trial without catheter should be opted for selective patients having Benign Prostatic Hyperplasia presenting with Acute Urinary Retention.